A new transform for document image compression - Aye Aung (2011)
In this paper, we propose a new real transform (rCS-SCHT) derived from the conjugate symmetric sequencyordered complex Hadamard transform (CS-SCHT) for document image compression. Like the CS-SCHT, the proposed transform is also an orthogonal transform. The transform computation is very simple and it requires only addition/subtractions with the use of a fast algorithm. This transform possesses good energy compaction property which makes it suitable to be employed in document image compression. Simulations are conducted in order to demonstrate the energy compaction capability of the transform as compared to the discrete cosine transform (DCT) and the Walsh Hadamard transform (WHT), particularly for scanned document images. Further discussions on the bit rate vs peak signal-to-noise (PSNR) performances of the proposed transform, the DCT and the WHT are presented using the default JPEG setting for simulations.